Factors Associated With the Development of Delirium in Elderly Patients in Intensive Care Units. Issue 4 (December 2015) - Lin, Wei-Li; Chen, Yi-Fan; Wang, Jeng
ABSTRACT: Background: High prevalence rates of delirium have been found in intensive care units (ICUs), ranging from 20% to 80%. The development of delirium may prolong length of stay, impair cognition, and result in placement in a nursing home for thepatient. Purpose: There is a lack of research focused on the aging population, so the purpose of this study was to establish the incidence rate of delirium among ICU elderly patients and to identify its risk factors. Methods: An observational design with repeated measures was used. Subjects older than 65 years who had been admitted to the ICU within 24 hours were recruited. The Confusion Assessment Method for the Intensive Care Unit and Richmond Agitation–Sedation Scale were used twice a day to identify subjects experiencing delirium by RA. The demographic data, history of illness, Acute Physiology and Chronic Health Evaluation II scores, and laboratory data of the participants were recorded. Results: Ninety participants were included from a medical ICU. The incidence rate of delirium was 75.6% ( n = 68). Average age was 78.28 ± 7.6 years; Acute Physiology and Chronic Health Evaluation II scores ranged from 7 to 35. Most participants were diagnosed with respiratory failure (73.3%), and 86.76% of participantsdeveloped delirium within 24 hours. The most frequently experienced type of delirium was the mixed subtype (47.05%); the second most frequently experienced was hypoactive next. The risk factors were analyzed using logistic regression. The numberof anesthetic analgesics used, total number of medications prescribed, duration of dehydration, use of corticosteroids before admissions, and shock were identified and explained 31.3% of variance. Conclusions/Implications for Practice: Delirium is a severe problem among elderly patients in the ICU. Healthcare professionals should pay more attention to elderly patients at greater risk for experiencing delirium.